MOF (Metal Organic Framework) membrane with in-hole MOF structure and preparation method of MOF membrane

By growing MOF-801 crystals in the membrane pores of the MOF-808 membrane, the pore size of the MOF-808 membrane is controlled, and the problem of difficult regulating the pore size of the MOF-808 membrane in the prior art is solved, and its wider application and performance improvement in the separation process is achieved.

CN119701672AActive Publication Date: 2025-03-28NANJING TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411796798.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the pore size of the MOF-808 membrane, which limits its application in the separation process.

Method used

Using the construction strategy of MOF-in-MOF membrane, MOF-801 crystals are grown in the membrane pores of MOF-808 membrane. By adjusting the concentration of Zr metal source in the MOF-801 raw material liquid and the molar ratio of Zr metal source to fumaric acid ligand, the growth of MOF-801 in the MOF-808 membrane is controlled, thereby regulating the membrane pore size.

Benefits of technology

The effective regulation of the pore size of MOF-808 membrane was successfully achieved, making it more widely applicable in different separation processes, and improving its performance in selective separation of H2 and CO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005176947170000011
    Figure HDA0005176947170000011
  • Figure HDA0005176947170000012
    Figure HDA0005176947170000012
  • Figure HDA0005176947170000021
    Figure HDA0005176947170000021
Patent Text Reader

Abstract

The invention discloses an MOF membrane with an in-hole MOF structure and a preparation method of the MOF membrane, and belongs to the technical field of synthesis of MOF materials. The invention provides a construction strategy of the MOF in MOF membrane, small MOF particles are successfully grown in MOF membrane pores with large pore diameters to control the pore diameters of the MOF membranes, and the growth condition in the pores is controlled by adjusting the molar ratio of raw materials in the synthesis process to further control the pore diameters of the membranes, so that application of the high-stability MOF membranes to different separation processes becomes possible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of MOF material synthesis, and in particular to a MOF membrane with a pore-MOF structure and a preparation method thereof. Background Art

[0002] Metal-organic frameworks (MOFs) are multifunctional porous materials that have been widely used in many fields such as catalysis, separation and gas storage due to their high specific surface area and designable pore size. Therefore, they have received great attention from researchers in related fields in the past few decades, and the number of MOF-related studies has continued to grow. To date, hundreds of thousands of different MOF structures have been successfully synthesized using a wide range of metal ions and organic ligands.

[0003] Each MOF has unique chemical and structural properties that are determined by the components it contains, metal ions (or clusters), organic linkers, and their inherent coordination interactions. These compositional and structural properties are two key factors that affect the basic properties and subsequent applications of MOFs. Therefore, choosing the appropriate metal and organic components is crucial to impart the desired properties to the final MOF, considering their inherent chemical and structural properties. Ultimately, producing MOFs with desired structures using ideal components is the best way to achieve optimal MOFs with desired properties, tailored for specific purposes. In addition, producing hybrid MOFs with complex compositions, structures, and morphologies can also provide great opportunities to obtain special MOFs with advanced properties and functionalities.

[0004] Zr-MOFs is a new type of MOFs material with variable topological structures and unique properties. It also has more organic ligand connection sites than other MOF materials. Among them, high-valent metal ions can be regarded as hard acids, while organic ligands can be regarded as hard bases. Based on the theory of hard and soft acids and bases, high-valent metal ions and organic ligands can form strong metal-ligand bonds, so Zr-MOFs have good stability and can be used for strict size screening. It is considered to be a porous material with great industrial application potential. MOF-808 is a typical Zr-MOFs material with excellent stability and high specific surface area. It has been used in gas storage, adsorption and catalysis. However, due to its large pore size, Due to its characteristics, this material is difficult to be well applied in most separation processes. At present, the research on MOF-808 materials mainly focuses on the optimization of synthesis methods and material modification. It is difficult to further effectively regulate the pore size of MOF-808 membranes so that they can be better used in different separation processes. Therefore, it is necessary to design effective strategies to regulate its pore size in a targeted manner. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the prior art and to provide a MOF membrane with a MOF structure in a pore. The present application is based on the strategy of MOF-in-MOF membrane, and small-pore MOF crystals are grown in a large-pore MOF membrane to effectively regulate the membrane pore size.

[0006] In order to achieve the above technical objectives, the present invention is implemented by the following technical solutions:

[0007] A MOF membrane with a MOF structure in pores comprises a base membrane and a selective separation layer on the surface of the base membrane, wherein the material in the selective separation layer is a first MOF crystal, and a second MOF crystal is distributed in the pores of the first MOF crystal.

[0008] The base film is a porous polymer film.

[0009] The first MOF crystal is MOF-808, and the second MOF crystal is MOF-801.

[0010] The method for preparing the MOF membrane having a MOF structure in the pores comprises the following steps:

[0011] Step 1, preparing a separation layer formed by a first MOF crystal on the surface of the base film;

[0012] Step 2, placing the membrane obtained in step 1 in a reaction solution containing a metal source and a ligand for synthesizing a second MOF crystal, taking it out and performing a hydrothermal synthesis at a high temperature to generate a second MOF crystal in the pores of the first MOF crystal;

[0013] Step 3, activating the membrane obtained in step 2.

[0014] The above-mentioned method for preparing the MOF membrane having a pore MOF structure comprises the following steps:

[0015] 1) Preparation of MOF-808 membrane and activation;

[0016] 2) dissolving the zirconium metal source and the fumaric acid ligand in a mixed solvent of water and acetic acid to obtain a MOF-801 raw material solution;

[0017] 3) soaking the activated MOF-808 membrane in the MOF-801 raw material solution prepared in step 2) for a period of time, taking it out, and placing it in an oven for hydrothermal reaction to obtain an unactivated MOF-801in MOF-808 membrane;

[0018] 4) Wash the unactivated MOF-801in MOF-808 membrane with deionized water and immerse it in deionized water, heat and dry it to obtain the activated MOF-801in MOF-808 membrane.

[0019] Furthermore, in the MOF-801 raw material solution prepared in step 2), the molar ratio of the zirconium metal source to the fumaric acid ligand is 1:1-3, preferably 1:2; the concentration of the zirconium metal source is 1-4 mmol / 50 mL, preferably 1 mmol / 50 mL; and the volume ratio of water to acetic acid in the mixed solvent is 3.5-4:1-1.5.

[0020] Furthermore, in step 3), the MOF-808 membrane is immersed in the MOF-801 raw material solution for 1 to 3 hours, the hydrothermal reaction temperature is 75 to 90° C., and the reaction time is 18 to 24 hours.

[0021] Furthermore, in step 4), the heating and drying temperature is 120-130° C., and the drying time is 12-24 hours.

[0022] Further, in step 1), the preparation process of MOF-808 membrane is as follows:

[0023] Ⅰ. Dissolve the zirconium metal source and fumaric acid ligand in a mixed solvent of N,N-dimethylformamide and formic acid respectively, then add the zirconium source solution and fumaric acid solution to both sides of the membrane device, and separate the device in the middle with a membrane support body, on which MOF-808 seed crystals are loaded;

[0024] II. Place the membrane-making device in an oven and heat it to react to obtain an unactivated MOF-808 membrane;

[0025] III. The unactivated MOF-808 membrane is subjected to solvent exchange treatment to obtain an activated MOF-808 membrane.

[0026] Furthermore, in step I, the volume ratio of N,N-dimethylformamide and formic acid in the mixed solvent is 3:2, and the membrane support is made of porous nylon.

[0027] Furthermore, in step II, the heating reaction temperature is 85-100° C. and the reaction time is 18-20 h.

[0028] Furthermore, in step III, the solvent exchange treatment process is as follows: the unactivated MOF-808 membrane is rinsed with DMF three times, washed with methanol five times, immersed in a methanol solution, and vacuum dried at 170° C. for 12 h to obtain an activated MOF-808 membrane.

[0029] Based on the construction strategy of MOF in MOF membrane, this application uses the above method to prepare a MOF-801in MOF-808 membrane, which is characterized by growing MOF-801 crystals in the membrane pores of the MOF-808 membrane to regulate the membrane pore size, thereby facilitating the application of the MOF-808 membrane in different separation processes. For example, it can be seen from the embodiment that this membrane can be effectively used in the selective separation of H2 and CO2.

[0030] The beneficial effects of the present invention are:

[0031] 1. This application proposes a construction strategy of MOF in MOF membrane. First, a dense and continuous MOF-808 membrane is prepared by the reverse diffusion method. Then, MOF-801 particles are grown in the membrane pores of the MOF-808 membrane by the hydrothermal reaction method to control the pore size, so that the MOF-808 membrane can be used for different separation processes.

[0032] 2. In the present application, the MOF-808 membrane is first immersed in the MOF-801 raw material solution for a period of time and then taken out for hydrothermal reaction. Compared with the method of immersing the MOF-808 membrane in the MOF-801 raw material solution and directly conducting an in-situ hydrothermal reaction, this treatment can avoid a large amount of MOF-801 growing on the surface of the MOF-808 membrane, ensuring that MOF-801 is successfully grown in the pores, thereby achieving successful regulation of the pore size of the MOF-808 membrane;

[0033] 3. The present application controls the growth of MOF-801 in the pores of the MOF-808 membrane by changing the concentration of the Zr metal source and the molar ratio of the Zr metal source and the Fum organic ligand in the MOF-801 raw material solution, thereby further controlling the pore size of the MOF-801 in the MOF-808 membrane;

[0034] 4. The method disclosed in this application can be used to effectively control the pore size of the MOF-808 membrane, which makes it possible to apply the MOF-808 membrane to different separation processes. Based on the good stability of MOF-808, the MOF-801in MOF-808 membrane disclosed in this application has good application prospects and a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the preparation process of MOF-801in MOF-808 membrane, wherein (1) is a schematic diagram of the preparation of MOF-808 membrane by the reverse diffusion method; (2-3) is a schematic diagram of the growth of MOF-801 particles in the pores of MOF-808 membrane;

[0036] Figure 2 1 is the SEM image of the porous nylon support at different seed loading amounts, wherein, panel a is the SEM image of the porous nylon support without seed loading; panel be is the SEM image of the porous nylon support with 0.15 mg, 0.30 mg, 0.45 mg, and 0.60 mg MOF-808 seed loading, respectively;

[0037] Figure 3Figure 1 is the SEM images of MOF-808 membranes prepared by reverse diffusion growth of MOF-808 on porous nylon supports with different MOF-808 seed loading amounts, wherein panels ab are the surface morphology and cross-sectional morphology of the MOF-808 membrane (denoted as M1) prepared by direct reverse diffusion growth of MOF-808 on a porous nylon support without seed loading, panels cd are the surface morphology and cross-sectional morphology of the MOF-808 membrane (denoted as M2) prepared by reverse diffusion growth of MOF-808 on a porous nylon support with 0.15 mg seed loading, respectively; panels ef are The surface morphology and cross-sectional morphology of the MOF-808 membrane (denoted as M3) prepared by reverse diffusion growth of MOF-808 on a porous nylon support loaded with 0.30 mg of seed crystals; the gh insets are the surface morphology and cross-sectional morphology of the MOF-808 membrane (denoted as M4) prepared by reverse diffusion growth of MOF-808 on a porous nylon support loaded with 0.45 mg of seed crystals; the ij insets are the surface morphology and cross-sectional morphology of the MOF-808 membrane (denoted as M5) prepared by reverse diffusion growth of MOF-808 on a porous nylon support loaded with 0.60 mg of seed crystals;

[0038] Figure 4 Panel a in the middle is the XRD pattern of the MOF-808 membrane and the MOF-808 powder generated in the reverse diffusion reaction; Panel b is the XRD pattern of the MOF-808 membrane prepared by reverse diffusion growth of MOF-808 on a porous nylon carrier with different MOF-808 seed loadings;

[0039] Figure 5 The SEM images of the MOF-808 membrane grown by reverse diffusion at different temperatures, wherein the ab images are the surface and cross-sectional morphologies of the MOF-808 membrane grown by reverse diffusion at 80°C; the cd images are the surface and cross-sectional morphologies of the MOF-808 membrane grown by reverse diffusion at 85°C; the ef images are the surface and cross-sectional morphologies of the MOF-808 membrane grown by reverse diffusion at 90°C; the gh images are the surface and cross-sectional morphologies of the MOF-808 membrane grown by reverse diffusion at 95°C;

[0040] Figure 6 It is the N2 adsorption / desorption isotherm of MOF-808 powder prepared by the reverse diffusion method at 77K;

[0041] Figure 7 This is the H2 and CO2 gas performance test diagram of the porous nylon support and MOF-808 membrane;

[0042] Figure 8Panels a and b are surface SEM images of the MOF-801in MOF-808 membrane prepared in Comparative Example 1; panels c and d are cross-sectional SEM images of the MOF-801in MOF-808 membrane prepared in Comparative Example 1;

[0043] Fig. 9 Panels a and b are surface and cross-sectional SEM images of the MOF-808 membrane used in Example 1, and panels c and d are surface and cross-sectional SEM images of the MOF-801in MOF-808 membrane prepared by growing MOF-801 in the pores of the MOF-808 membrane in Example 1;

[0044] Fig.10 The middle panel a is the XRD comparison diagram before and after the growth of MOF-801 in the pores of MOF-808 membrane; the middle panel b is the water contact angle test diagram, where Nylon: porous nylon support; MOF-808: MOF-808 membrane; 801in 808: MOF-801in MOF-808 membrane;

[0045] Fig.11 Figure a in the middle shows the N2 adsorption / desorption isotherms of MOF-801in MOF-808 membranes generated with different Zr metal source concentrations at 77K when the molar ratio of Zr metal source to Fum organic ligand is 1:1; Figure b shows the pore size and specific surface area statistics of MOF-801in MOF-808 membranes generated with different Zr metal source concentrations when the molar ratio of Zr metal source to Fum organic ligand is 1:1. 1Zr corresponds to the adsorption curve of 1eq Zr in Figure a, representing the use of a metal source with a concentration of 1mmol / 50mL. The explanations for 2Zr, 3Zr, and 4Zr are similar; Figure c shows the MOF-801in MOF-808 membranes generated with different Zr metal source concentrations when the molar ratio of Zr metal source to Fum organic ligand is 1:2. N2 adsorption / desorption isotherms of MOF-808 membrane at 77K; d is a statistical diagram of the pore size and specific surface area of ​​MOF-801in MOF-808 membrane generated with different Zr metal source concentrations when the molar ratio of Zr metal source to Fum organic ligand is 1:2. 1Zr corresponds to the adsorption curve of 1eq Zr in c, which means that the metal source concentration is 1mmol / 50mL. The explanation of 4Zr is similar.

[0046] Fig.12 These are the H2 and CO2 gas performance test graphs of the MOF-808 membrane used in Example 1 and the MOF-801in MOF-808 membrane synthesized with different molar ratios of Zr metal source and Fum organic ligand as MOF-801 reactants, wherein 801-808 refers to MOF-801in MOF-808 membrane, and the concentration of the Zr metal source for preparing MOF-801 is 4 mmol / 50 mL. DETAILED DESCRIPTION

[0047] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0048] Preparation of MOF-808 membrane by reverse diffusion method to explore the optimal conditions for membrane preparation

[0049] 1) 363 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O) and 1182 mg of trimesic acid (BTC, C9H6O6) were dissolved in a mixed solvent of DMF / formic acid (45 / 30 mL), respectively. The zirconium source solution and the trimesic acid solution were added to the left and right sides of the U-shaped glass membrane device, respectively. The middle of the device was separated by a porous nylon support, wherein the porous nylon support was loaded with different amounts of MOF-808 seeds (the loading amounts were 0, 0.15, 0.3, 0.45 and 0.60 mg, respectively) by filtering 100 mL of deionized water solution containing different amounts of MOF-808 powder.

[0050] 2) The membrane-making device was placed in an oven and reacted at 95°C for 18 hours. During the membrane-making process, the MOF particles formed in the solution were also collected for characterization;

[0051] 3) The prepared sample was first rinsed with DMF three times, then washed with methanol five times and immersed in a methanol solution, and finally vacuum dried at 170° C. for 12 h to obtain an activated MOF-808 membrane or MOF-808 powder.

[0052] Performance test of MOF-808 membrane:

[0053] 1) Effect of different amounts of seed crystals loaded on the carrier on MOF-808 membrane

[0054] The porous nylon support has the advantages of good thermal stability and chemical stability, low cost, and low transmission resistance. It has a certain tolerance to the solvent DMF used in the experiment and is low in cost, so it is used as the porous support for growing MOF-808 membrane ( Figure 2 (a, small figure).

[0055] The MOF-808 membrane grown directly on the porous nylon support without seed loading by the reverse diffusion method cannot form a complete membrane layer. Only a small amount of MOF-808 particles appear on the surface of the porous nylon support ( Figure 3 (a, b, and c).

[0056] However, after loading MOF-808 seeds on the porous nylon support and then growing the MOF-808 membrane by reverse diffusion, a dense and continuous MOF-808 membrane layer can be grown. It can be considered that the addition of MOF-808 seeds can overcome the bottleneck of nucleation reaction between Zr metal clusters (Secondary building units, SBU) and BTC organic ligands, reduce the difficulty of crystal nucleation, and enable it to form a dense membrane layer. Figure 3 The small figures in the middle cj are morphological pictures of MOF-808 membranes synthesized under different conditions of seed loading on the porous nylon support. It can be seen from the figure that the seed loading on the porous nylon support has no obvious effect on the morphology of the MOF-808 membrane.

[0057] XRD characterization revealed that the MOF-808 membrane (seed loading of 0.45 mg) grown by reverse diffusion and the powder generated in the process all had MOF-808 characteristic peaks, and the MOF-808 membrane also contained a porous nylon support with a peak shape of 15 to 30° ( Figure 4 At the same time, we also tested the XRD of MOF-808 films synthesized at different seed loadings and found that they all had the same MOF-808 characteristic peaks ( Figure 4 (B), where no film is formed without seed loading, the peak shape that appears is different from the characteristic peak of MOF-808, which can be considered to be caused by incomplete crystal nucleation reaction.

[0058] 2) The MOF-808 membranes targeted by subsequent tests were prepared based on porous nylon supports with a seed loading of 0.45 mg. The main purpose was to study the effects of different reaction temperatures on the formation of MOF-808 membranes. The initial raw material preparation process and the assembly process of the reaction solution and the porous nylon support remained unchanged. The assembled zirconium source solution, fumaric acid solution and porous nylon support were placed in an oven and reacted at 80, 85, 90 and 95°C for 18 hours. During the membrane preparation process, the MOF particles formed in the solution were also collected for characterization. The prepared samples were first rinsed with DMF 3 times, then washed with methanol 5 times and immersed in a methanol solution. Finally, they were vacuum dried at 170°C for 12 hours to obtain the activated MOF-808 membrane or MOF-808 particles.

[0059] refer to Figure 5, the MOF-808 membrane surface grown by reverse diffusion at 80℃ has obvious intergranular defects and most of the membrane is only a large number of MOF-808 particles accumulated, the membrane thickness is less than 1um and discontinuous, and as the temperature rises, the intergranular defects on the surface of the MOF-808 membrane grown by reverse diffusion at 85℃ begin to decrease, and there is an obvious film layer; when the temperature continues to rise to 90℃, the membrane surface shows obvious MOF-808 crystal structure, without obvious intergranular defects. When the temperature is 95℃, the membrane surface is dense and defect-free, and the membrane layer is uniform and continuous. It can be seen that temperature can promote the nucleation reaction of Zr metal clusters SBU and BTC organic ligands, and increasing the temperature can make them react into a continuous film layer.

[0060] 3) Based on the above tests, the MOF-808 membrane targeted by subsequent tests was prepared based on a porous nylon support with a seed loading of 0.45 mg and a back diffusion temperature of 95°C; MOF-808 powder was also prepared under the corresponding conditions.

[0061] The BET test of MOF-808 powder generated in the reverse diffusion process showed that its specific area was 2429m 2 g -1 The average pore size is ( Figure 6 )

[0062] The MOF-808 membrane was tested for H2 and CO2 gases, and it was found that compared with the porous nylon support with a pore size of 100 nm, the prepared MOF-808 membrane had an order of magnitude decrease in the gas flux of CO2 and H2, from 2.14×10 8 Reduced to 7.82×10 6 GPU, and the selectivity has been increased from 1.50 to 4.23 ( Figure 7 ). It can be considered that H2 and CO2 diffuse freely on the porous nylon support with large pores (100 nm), so the selectivity is approximately 1. The diffusion on the MOF-808 membrane is Knudsen diffusion, so its selectivity is approximately the ideal selectivity (4.7) of CO2 and H2 Knudsen diffusion.

[0063] Example 1

[0064] This embodiment discloses a method for preparing a MOF-801in MOF-808 membrane, which specifically comprises the following steps:

[0065] 1) 363 mg ZrOCl2﹒8H2O and 1182 mg BTC ligand were dissolved in a mixed solvent of DMF / formic acid (45 / 30 mL), and the zirconium source solution and the trimesic acid solution were added to the left and right sides of the U-shaped glass membrane device, respectively. The middle of the device was separated by a porous nylon support, wherein the porous nylon support was loaded with 0.45 mg MOF-808 seeds by filtering a deionized water solution containing MOF-808 powder;

[0066] 2) Place the film-making device in an oven and react at 95°C for 18 hours;

[0067] 2. Preparation of MOF-801in MOF-808 membrane by hydrothermal method

[0068] 1) After the reaction is completed, the MOF-808 membrane taken out from the U-shaped glass membrane device is soaked and washed with methanol for 5 times, and then soaked and washed with deionized water for 3 times to remove the residual solvent.

[0069] 2) Dissolve ZrOCl2﹒8H2O and fumaric acid in water / acetic acid (V 水 :V 乙酸 =3.7:1.3) in a mixed solvent, the concentration of the Zr metal source is 1 mmol / 50 mL, and the molar ratio of the Zr metal source to the Fum organic ligand is 1:1;

[0070] 3) Soaking the washed MOF-808 membrane in the solution prepared in step 2) for 3 hours, taking it out and placing it in an oven, reacting it at 80° C. for 20 hours, to obtain an unactivated MOF-801in MOF-808 membrane;

[0071] 4) Dissolve ZrOCl2﹒8H2O and different contents of fumaric acid in water / acetic acid (V 水 :V 乙酸 =3.7:1.3) mixed solvent, soak MOF-808 powder in the solution for 3 hours, then take it out and put it in an oven, react at 80°C for 20 hours to obtain unactivated MOF-801in MOF-808 powder;

[0072] 5) The unactivated MOF-801in MOF-808 membrane and the unactivated MOF-801in MOF-808 powder were washed three times with deionized water and then immersed in a deionized water solution, and finally vacuum dried at 120° C. for 12 h to obtain the activated MOF-801in MOF-808 membrane or powder.

[0073] Example 2

[0074] The difference between Example 2 and Example 1 is that in step 2) ZrOCl2﹒8H2O and fumaric acid are dissolved in water / acetic acid (V 水 :V 乙酸 =3.7:1.3) in the mixed solvent, the concentration of Zr metal source is 2 mmol / 50 mL, and the molar ratio of Zr metal source to Fum organic ligand is 1:1.

[0075] Example 3

[0076] The difference between Example 3 and Example 1 is that in step 2) ZrOCl2﹒8H2O and fumaric acid are dissolved in water / acetic acid (V 水 :V 乙酸 =3.7:1.3) in the mixed solvent, the concentration of Zr metal source is 3 mmol / 50 mL, and the molar ratio of Zr metal source to Fum organic ligand is 1:1.

[0077] Example 4

[0078] The difference between Example 4 and Example 1 is that in step 2) the ZrOCl2﹒8H2O and fumaric acid are dissolved in water / acetic acid (V 水 :V 乙酸 =3.7:1.3) in the mixed solvent, the concentration of Zr metal source is 4 mmol / 50 mL, and the molar ratio of Zr metal source to Fum organic ligand is 1:1.

[0079] Example 5

[0080] The difference between Example 5 and Example 1 is that in step 2) ZrOCl2﹒8H2O and fumaric acid are dissolved in water / acetic acid (V 水 :V 乙酸 =3.7:1.3) in the mixed solvent, the concentration of the Zr metal source is 1 mmol / 50 mL, and the molar ratio of the Zr metal source to the Fum organic ligand is 1:2.

[0081] Example 6

[0082] The difference between Example 6 and Example 1 is that in step 2) ZrOCl2﹒8H2O and fumaric acid are dissolved in water / acetic acid (V 水 :V 乙酸 =3.7:1.3) in the mixed solvent, the concentration of Zr metal source is 4 mmol / 50 mL, and the molar ratio of Zr metal source to Fum organic ligand is 1:2.

[0083] Comparative Example

[0084] The difference between this comparative example and Example 1 is that the MOF-808 membrane is directly immersed in the raw material solution of MOF-801 to carry out the traditional in-situ hydrothermal reaction to grow MOF-801 particles (the scheme of taking out the membrane from the immersion solution after immersion and then carrying out the hydrothermal reaction is not adopted), the in-situ hydrothermal reaction temperature is also 80°C, and the reaction time is 20 hours.

[0085] Related performance tests:

[0086] The test found that the MOF-801 grown by the in-situ hydrothermal method in the comparative example generated a new membrane layer on the basis of the original MOF-808 membrane, and a structure similar to a double-layer membrane appeared ( Figure 8 c and d), and there are a large number of MOF-801 particles on the surface ( Figure 8 In the middle a and b panels, the film thickness has increased significantly compared to the original MOF-808 membrane, from ~2um to ~3um. When using the in-situ hydrothermal method, most of the MOF-801 is preferentially generated in the reaction solution rather than in the pores of the MOF-808 membrane, resulting in a large amount of MOF-801 growing on the surface of the MOF-808 membrane and even growing a double-layer membrane structure.

[0087] In the embodiment, a scheme of soaking first and then taking out for hydrothermal reaction is adopted. When the MOF-808 membrane is immersed in the MOF-801 raw material solution, the MOF-801 raw material solution is adsorbed into the MOF-808 pores. After soaking for a period of time, the membrane adsorbed with the raw material solution is taken out separately for reaction, and MOF-801 crystals can be grown in the pores.

[0088] refer to Fig. 9 The surface morphology and thickness of the membrane prepared by the method used in Example 1 did not change significantly compared with the MOF-808 membrane.

[0089] XRD test was performed on the MOF-801in MOF-808 film prepared in Example 1. The results are shown in Table 1. Fig.10 In the middle panel a, it is found that after MOF-801 grows in the membrane pores of the MOF-808 membrane, the first peak in the double peak at ~8° shows a significant increase, which can correspond to the characteristic peak of MOF-801, indicating the successful introduction of MOF-801.

[0090] The water contact angle of MOF-801in MOF-808 membrane was tested. The porous nylon support itself is hydrophilic. After the MOF-808 membrane was grown on its surface, it showed a water contact angle of 117.75° due to the hydrophobicity of MOF-808. However, after MOF-801 was grown in the membrane pores of the MOF-808 membrane, the contact angle decreased to 100.42° ( Fig.10This is because MOF-801 is hydrophilic, so the water contact angle decreases after MOF-801 grows inside the pores of MOF-808.

[0091] In Examples 1-4, as the reactants for preparing MOF-801, the molar ratio of the Zr metal source and the Fum organic ligand was 1:1, but the reactant concentration gradually increased. As the reactant concentration gradually increased from 1mmol / 50mL to 4mmol / 50mL, the pore size and specific surface area of ​​the MOF-808 membrane became smaller. When the reactant concentration was 1mmol / 50mL, the pore size was greatly reduced to The specific surface area is greatly reduced to 475m 2 g -1 ; When the concentration was increased to 2mmol / 50mL, the pore size was further reduced to The specific surface area no longer changes significantly; when the concentration is further increased, the pore size no longer decreases significantly, and the specific surface area no longer has a significant change trend ( Fig.11 a and b insets).

[0092] In order to explore whether the pore size can be further reduced, in Example 5-6, the molar ratio of the Zr metal source and the Fum organic ligand for preparing MOF-801 was set to 1:2, and the concentration of the Zr metal source was increased from 1 mmol / 50 mL to 4 mmol / 50 mL. The results are shown in Fig.11 In the middle cd panel, at the same Zr metal source concentration (1mmol / 50mL), the pore size of the MOF-808 membrane is further reduced to When the Zr metal source concentration is further increased, the pore size no longer decreases significantly. When the Zr metal source concentration is 4 mmol / 50 mL, the pore size of the MOF-808 membrane is adjusted to

[0093] Under the condition of fixed reactant ratio, when the reactant concentration is gradually increased to a certain value, the reason why the pore size no longer changes significantly may be because the space inside the pores of the MOF-808 membrane is limited. After reaching a certain reactant concentration, the space inside the pores has been close to saturation with the adsorption of reactants. Therefore, after continuing to increase the concentration, the number of MOF-801 particles growing in the pores no longer increases significantly, so the pore size no longer changes significantly. The reason why the effect of increasing the molar ratio of Zr metal source and Fum organic ligand to 1:2 on the reduction of pore size is more significant may be because excessive Fum organic ligands are conducive to the growth of MOF-801. This is because each Zr6O4(OH)4(-CO2) in the MOF-801 crystal structure 12 The metal cluster has 12 Fum organic ligand binding sites, and its structure is analogous to the 'kissing sphere number problem' in three-dimensional space, which is the most compact packing mode of SBUs.

[0094] The MOF-801inMOF-808 membranes prepared with different molar ratios of Zr metal source and Fum organic ligand were tested with CO2 and H2 gases, and it was found that their flux was an order of magnitude lower than that of MOF-808 membranes ( Fig.12 ). When the Zr metal source and Fum organic ligand were used as MOF-801 reactants in an equal molar ratio, the flux of the prepared MOF-801inMOF-808 membrane was reduced to 6.93×10 5 GPU, the selectivity is 4.28, which is not a particularly significant improvement. This is because the membrane pore size is ( Fig.11 b) is much larger than CO2 and H2 Therefore, the diffusion mode is still dominated by Knudsen diffusion. However, when the molar ratio of Zr metal source and Fum organic ligand increases to 1:2, the flux of the prepared MOF in MOF membrane has dropped to 2.16×10 4 GPU, selectivity is 5.59. At this time, the membrane pore size is ( Fig.11 In the middle (small picture d), the diffusion is still dominated by Knudsen diffusion. However, the selectivity exceeds the Knudsen diffusion selectivity. This is because the MOF material has a unique interaction force with CO2, which makes it have a higher adsorption capacity for CO2 and allows H2 to pass through preferentially, so it has a certain selectivity.

Claims

1. A MOF membrane having a MOF structure in a hole, characterized in that: It includes a base film and a selective separation layer on the surface of the base film. The material in the selective separation layer is a first MOF crystal, and a second MOF crystal is distributed in the pores of the first MOF crystal.

2. The MOF membrane having a MOF structure in a hole according to claim 1, characterized in that: The base film is a porous polymer film; the first MOF crystal is MOF-808, and the second MOF crystal is MOF-801.

3. The method for preparing a MOF membrane having a MOF structure in a hole according to claim 1, characterized in that: The steps include: Step 1, preparing a separation layer formed by a first MOF crystal on the surface of the base film; Step 2, placing the membrane obtained in step 1 in a reaction solution containing a metal source and a ligand for synthesizing a second MOF crystal, taking it out and performing a hydrothermal synthesis at a high temperature to generate a second MOF crystal in the pores of the first MOF crystal; Step 3, activating the membrane obtained in step 2.

4. The method for preparing a MOF membrane having a MOF structure in a hole according to claim 3, characterized in that: The steps include: 1) Preparation of MOF-808 membrane and activation; 2) dissolving the zirconium metal source and the fumaric acid ligand in a mixed solvent of water and acetic acid to obtain a MOF-801 raw material solution; 3) soaking the activated MOF-808 membrane in the MOF-801 raw material solution prepared in step 2) for a period of time, taking it out, and placing it in an oven for hydrothermal reaction to obtain an unactivated MOF-801in MOF-808 membrane; 4) Wash the unactivated MOF-801in MOF-808 membrane with deionized water and immerse it in deionized water, heat and dry it to obtain the activated MOF-801in MOF-808 membrane.

5. The method for preparing a MOF membrane having a MOF structure in a hole according to claim 4, characterized in that: In the prepared MOF-801 raw material solution in step 2), the molar ratio of the zirconium metal source to the fumaric acid ligand is 1:1-3, and the concentration of the zirconium metal source is 1-4 mmol / 50 mL; the volume ratio of water to acetic acid in the mixed solvent is 3.5-4:1-1.

5.

6. The method for preparing a MOF membrane having a MOF structure in a hole according to claim 4, characterized in that: In step 3), the MOF-808 membrane is immersed in the MOF-801 raw material solution for 1 to 3 hours, the hydrothermal reaction temperature is 75 to 90° C., and the reaction time is 18 to 24 hours.

7. The method for preparing a MOF membrane having a MOF structure in a hole according to claim 4, characterized in that: In step 4), the heating and drying temperature is 120-130° C., and the drying time is 12-24 hours.

8. The method for preparing a MOF membrane having a MOF structure in a hole according to claim 4, characterized in that: In step 1), the preparation process of MOF-808 membrane is as follows: Ⅰ. Dissolve the zirconium metal source and trimesic acid ligand in a mixed solvent of an organic solvent and formic acid, respectively. Then, add the zirconium source solution and trimesic acid solution to both sides of the membrane device. The middle of the device is separated by a membrane support body, and the membrane support body is loaded with MOF-808 seed crystals. II. Place the membrane-making device in an oven and heat it to react to obtain an unactivated MOF-808 membrane; III. The unactivated MOF-808 membrane is subjected to solvent exchange treatment to obtain an activated MOF-808 membrane.

9. The method for preparing a MOF membrane having a MOF structure in a hole according to claim 8, characterized in that: In step I, the volume ratio of the organic solvent to formic acid in the mixed solvent is 3:2, and the membrane support is made of porous nylon; in step II, the heating reaction temperature is 85-100°C and the reaction time is 18-20h; In step III, the solvent exchange treatment process is as follows: the unactivated MOF-808 membrane is rinsed with DMF three times, washed with methanol five times, immersed in a methanol solution, and vacuum dried at 170° C. for 12 h to obtain an activated MOF-808 membrane.

10. Use of the MOF membrane having a MOF structure in the pores as claimed in claim 1 in selective separation of a gas mixture.

Citation Information

Patent Citations

  • Method for preparing MOF (at) MOF hybrid membrane by using two-dimensional nanosheet membrane induced heteroepitaxial growth method

    CN112657350A

  • Diaphragm, preparation method thereof and chemical battery

    CN112670664A

  • Preparation method of nano-porous carbon ceramic membrane nanofiltration composite membrane

    CN113289501A

  • Method for preparing Zr-MOF molecular sieve membrane by using zirconium cluster as metal source under mild reaction condition

    CN114887502A

  • Composite porous body and method of manufacturing the same

    JP2014036935A